Efficacy and safety of the metformin-mazindol anorectic combination in rat - Argüelles-Tello Federico; Roa-Coria José Eduardo; Zúñiga-Romero Ángel; Huerta-Cruz Juan Carlos; Quiñonez-Bastidas Geovanna Nalley; Flores-Murrieta Francisco Javier; Rocha-González Héctor Isaac; Reyes-García Juan Gerardo (Acta Pharmaceutica)
The current study investigates the anorectic interaction and safety of the mazindol-metformin combination in rats. Isobologram and interaction index were used to determine anorectic interaction between mazindol and metformin in the sweetened milk model. The safety profile of the mazindol-metformin combination was determined by measuring anxiety, blood pressure, hematic biometry and blood chemistry. An acute dose of mazindol and metformin administered per os, individually or as a mixture, has reduced the milk consumption in rats in a dose-dependent manner. Theoretical effective dose 40 (ED40t) did not differ from the experimental effective dose 40 (ED40e) obtained with the mazindol-metformin mixture in the anorexia experiments, by Student′s t-test. In addition, the interaction index confirmed the additive anorectic effect between both drugs. A single oral dose of ED40e mazindol-metformin mixture induced anxiolysis in the elevated plus-maze test. Moreover, oral administration of mazindol-metformin combination for 3 months significantly decreased glycemia, but not blood pressure nor other parameters of hematic biometry and blood chemistry. Results suggest that mazindol-metformin combination exerts an additive anorectic effect, as well as anxiolytic and hypoglycemic properties. Mazindol-metformin combination might be useful in obese patients with anxiety disorders or diabetes risk factors.